The Role of Organizational Culture in Improving the Service Quality of Import Forwarding Companies - Zulkifli Zainuddin (Journal Of Applied Multidisiplinary Studies, 2026)
This study aims to determine the influence of organizational culture on the quality of import forwarding company services. The research method used is a quantitative approach with data collection techniques through distributing questionnaires to 44 employee respondents of PT Mitra Transindo Perkasa. Data were analyzed using IBM SPSS version 21 through validity tests, reliability tests, simple linear regression analysis, t-tests, and coefficient of determination (R²). The results of the study indicate that organizational culture has a positive and significant effect on the quality of import forwarding company services with a significance value of 0.000 <0.05. The coefficient of determination (R²) value of 0.343 indicates that organizational culture contributes 34.3% to the quality of import forwarding company services, while the rest is influenced by other factors outside the study. A good organizational culture can improve internal communication, work discipline, teamwork, and service orientation, thereby supporting the improvement of the company's service quality. This study shows that organizational culture is one of the important factors in increasing the effectiveness of service and the competitiveness of import forwarding companies in the logistics industry.